A randomized evaluation of simulation training on performance of vascular anastomosis on a high-fidelity in vivo model: the role of deliberate practice - Price, Joel; Naik, Viren; Boodhwani, Munir; Brandys, Tim; Hendry, Paul; Lam, Buu-Khanh (The Journal of thoracic and cardiovascular surgery, 2011)
There is mounting evidence supporting the benefit of surgical skills practice in a simulated environment. However, the use of simulation in cardiac surgical training has been limited. The purpose of the current trial was to examine the effect of independent and deliberate simulator practice, during nonclinical time, on the performance of an end-to-side microvascular anastomosis in an in vivo model. This single-blinded, randomized controlled trial received institutional review board approval. Thirty-nine first- and second-year surgical trainees were randomized to an expert-guided tutorial on a procedural trainer or to the expert-guided tutorial combined with self-directed practice on the same procedural trainer. Self-directed practice consisted of 10 anastomoses performed on the procedural trainer: a low-fidelity, commercially available bench model using 4-mm polytetrafluoroethylene graft as simulated blood vessel. Two weeks after the tutorial, subjects performed an end-to-side anastomosis in a live porcine model, under realistic operating room conditions. Assessment of outcomes was performed by 2 blinded, expert observers, uings validated measurements of technical skill. The primary outcome was the score on the Objective Structured Assessment of Technical Skill (OSATS) scale. Secondary outcomes included an anastomosis-specific end-product evaluation and time to completion. Statistical analysis was conducted using nonparametric, univariate techniques. Compared with residents who received expert-guided simulator training alone, those who in addition practiced on a simulator independently after hours scored significantly higher on the OSATS scale (23.7 ± 4.7 vs 18.5 ± 3.9, P = .003). Residents who practiced independently also scored significantly higher on the end-product evaluation (11.4 ± 3.2 vs 8.9 ± 2.1, P = .02) and performed the anastomosis significantly faster (777 seconds vs 977 seconds, P = .04). Interrater reliability was high between the expert observers (intraclass correlation coefficient = 0.8). Residents who had the opportunity for self-directed simulator practice performed an end-to-side anastomosis more adeptly, more quickly, and with a higher quality end product. The results of this randomized trial suggest that independent training on a procedural trainer did transfer to improved performance in an operating room environment. Simulator training should be incorporated into cardiovascular surgical curricula and residents should have access to this modality for independent after-hours practice to improve operating room performance.